What is the Trident for? Nuclear Deterrence and the Role of British Nuclear Weapons - Ritchie, Nick (2008)
Yes === This report supports the second in a series of briefings on Trident to be published during 2007 and 2008 as part of the Bradford Disarmamenet Research Centre's programme on Nuclear-Armed Britain: A Critical Examination of Trident Modernisation, Implications and Accountability.